Challenges and opportunities in the regulatory landscape of genetically modified crops in the European Union - Garcia-Alonso, Monica; Alcalde, Esteban; Criel, Ine; Novillo, Concepción; Kostolaniova, Petra; Podevin, Nancy (Frontiers in Bioengineering and Biotechnology, 2025)
Genetically modified (GM) crops, introduced in the mid-1990s, have undergone extensive scientific scrutiny over the past three decades. While initial regulatory frameworks were stringent due to the nascent nature of the technology and uncertainty regarding their safety, subsequent comprehensive research and independent risk assessments have consistently affirmed their safety for human, animal, and environmental health, leading to widespread global adoption. GM crops have demonstrably enhanced agricultural productivity, mitigated environmental impacts associated with conventional farming, and contribute to the United Nations Sustainable Development Goals. Consequently, many nations have refined their regulatory approaches based on accumulated scientific evidence. However, the European Union (EU) presents a contrasting scenario. Despite significant investments in agricultural biotechnology research and a commitment to the Sustainable Development Goals, the EU’s regulatory landscape for GM crops has become increasingly complex, effectively limiting European farmers’ access to these technologies. The EU heavily relies on imports of GM-containing protein-rich crops, while its farmers cannot benefit from their cultivation. The current pre-market assessment for GM crop import and food and feed use authorization is characterized by its lengthy, costly, and unpredictable nature. This paper discusses some of the issues faced by developers when trying to obtain import approvals for GM crops in the EU and the impact that the current regulatory framework is having on innovation. The authors propose a series of practical and feasible adjustments that could be implemented during the EU’s risk assessment process to unlock the benefits of biotechnology for European agriculture without compromising safety standards.